The Abnormal Proliferation of Hepatocytes is Associated with MC-LR and C-Terminal Truncated HBX Synergistic Disturbance of the Redox Balance - Cai, Dong-Mei; Mei, Fan-Biao; Zhang, Chao-Jun; An, San-Chun; Lv, Rui-Bo; Ren, Guan-Hua; Xiao, Chan-Chan; Long, Long; Huang, Tian-Ren; Deng, Wei (Journal of hepatocellular carcinoma, 2022)
Microcystin-LR (MC-LR) and hepatitis B virus (HBV) are associated with hepatocellular carcinoma (HCC). However, the concentrations of MC-LR in drinking water and the synergistic effect of MC-LR and HBV on hepatocellular carcinogenesis through their disturbance of redox balance have not been fully elucidated. We measured the MC-LR concentrations in 168 drinking water samples of areas with a high incidence of HCC. The relationships between MC-LR and both redox status and liver diseases in 177 local residents were analyzed. The hepatoma cell line HepG2 transfected with C-terminal truncated hepatitis B virus X gene (Ct-HBX) were treated with MC-LR. Reactive oxygen species (ROS), superoxide dismutase (SOD), glutathione (GSH) and malondialdehyde (MDA) were measured. Cell proliferation, migration, invasion, and apoptosis were assessed with cell activity assays, scratch and transwell assays, and flow cytometry, respectively. The mRNA and protein expression-related redox status genes were analyzed with qPCR and Western blotting. The average concentration of MC-LR in well water, river water and reservoir water were 57.55 ng/L, 76.74 ng/L and 132.86 ng/L respectively, and the differences were statistically significant (P < 0.05). The MC-LR levels in drinking water were correlated with liver health status, including hepatitis, clonorchiasis, glutamic pyruvic transaminase abnormalities and hepatitis B surface antigen carriage (all P values < 0.05). The serum MDA increased in subjects who drank reservoir water and were infected with HBV (P < 0.05). In the cell experiment, ROS increased when Ct-HBX-transfected HepG2 cells were treated with MC-LR, followed by a decrease in SOD and GSH and an increase in MDA. MC-LR combined with Ct-HBX promoted the proliferation, migration and invasion of HepG2 cells, upregulated the mRNA and protein expression of gene, and downregulated and genes. MC-LR and HBV may synergistically affect redox status and play an important role in hepatocarcinoma genesis.